Measurement of serum nitrite/nitrate concentration using high-performance liquid chromatography - I. El Menyawi (2018)
Previous studies have reported increased serum concentrations of nitrite/nitrate - the degradation products of nitric oxide - in Plasmodium vivax malaria and uncomplicated Plasmodium falciparum malaria. In all these studies, however, nitrite/nitrate has been measured spectrometrically using Griess reagent which carries major disadvantages in the determination of serum nitrite/nitrate. The method does not allow an exact differentiation of nitrite and biogenic amines that are physiologically present in plasma. In the present study we introduce high-performance liquid chromatography as a new, accurate and cost effective method for determination of serum nitrite/nitrate levels. Significantly increased nitrate concentrations were found in malaria patients and serum values remained above normal levels for at least 21 days. It could be shown that our HPLC method is a sensitive and cost-effective method for direct determination of nitrite/nitrate in serum samples, which is not influenced by the presence of biogenic amines.